PENGARUH IDENTITAS SOSIAL SEBAGAI PEGAWAI SENIOR, KARAKTERISTIK PEKERJAAN, DUKUNGAN SOSIAL, DAN KEJENUHAN PADA SIKAP PEGAWAI TENTANG PEKERJAAN DAN PENSIUN - Mamik Setiyorini (Magister Manajemen Fakultas Ekonomi dan Bisnis UNS, 2014)
The aim of this research is to investigate the relationship between perceived sosial identity as an older worker, job characteristic, social support and burnout and attitude towards retirement and work. A total of 400 questionnaires were collected from workers over the aged of 50, and they were working in Ministry of Communication and Information, Jakarta. Purposive sampling were used in this research. Stuctural Equation Model (SEM) analyses were performed to test the influence of social identity as an older worker, job characteristic, social support and burnout to attitude towards retirement and work. Age, gender, marital status and education were used as demographics variables. The result show that identification with older worker was positively related to intergenerational competition, and negatifly related to career development, bridge employment, devaluation work dan intention to early retirement. Intergroup permeability was positively related to intention to early retirement. Job characteristic was positively related to career development, intergenerational competition, bridge employment, devaluation work, burnout and intention to early retirement. Social support was negatifly related to burnout, and burnout was positively related to intention to early retirement. Intergroup permeability was not related to career development, intergenerational competition, bridge employment and devaluation work because older worker in this research felt intergroup unpermeability. It means older workers in this study feel the ageism and burnout at their workplace.